Characterization of polycyclic aromatic hydrocarbons in soil in a coal mining area, East China: Spatial distribution, sources, and carcinogenic risk assessment - Ren, Mengxi; Zheng, Liugen; Hu, Jie; Chen, Xing; Zhang, Yanhai; Dong, Xianglin; Wei, Xiangping; Cheng, Hua (Frontiers in Earth Science, 2022)
The polycyclic aromatic hydrocarbon (PAH) pollution process in mining areas, particularly coal mining areas, has accelerated because of coal chemical production and gangue accumulation. In this study, PHAs concentrations in surface soil was determined via gas chromatography–mass spectrometry. The composition, spatial distribution and sources of PAHs were analyzed, and their potential carcinogenic risks were evaluated.Results showed a wide PAH concentration range (218–1548 ng g−1). The high molecular weight proportion in contaminated areas was significantly higher than in uncontaminated areas. Clear differences in PAH distribution were detected in contaminated areas, with higher concentrations in the soils near an industrial park and coal gangue piles. The results of positive matrix factorization (PMF) in contaminated area revealed that coking, oil and biomass combustion, and vehicle emissions and coal combustion, contributed 31%, 26%, 24%, and 19%, respectively, to the detected PAHs. In contrast with the 10% contribution rate of the coking source in uncontaminated areas. The Monte Carlo method was used to assess the cancer risk to residents in the study areas. The carcinogenic health risk values for adults in the contaminated areas was higher than the safety standard (2.92 × 10−6) prescribed by the United States Environmental Protection Agency at 95% confidence level. Sensitivity analysis showed that the relative exposure duration (ED) and soil surface area of skin exposure were the most significant parameters for adults, and ED and body weight for children. The cancer risk for both adults and children in contaminated areas was five times than that in uncontaminated areas.